2014
DOI: 10.3349/ymj.2014.55.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Primary Epstein Barr Virus Hepatitis with Elevation of Alkaline Phosphatase and γ-Glutamyltransferase in Children

Abstract: PurposeThe aim of the present study was to evaluate the clinical characteristics of the primary Epstein-Barr virus (EBV) hepatitis with elevation of both serum alkaline phosphatase (ALP) and γ-glutamyltransferase (γ-GT) levels in children.Materials and MethodsA retrospective study was performed by reviewing of the medical records of 36 patients who were diagnosed with primary EBV hepatitis. The patients were divided into 2 groups: patients with elevated serum ALP and γ-GT levels (group 1) and patients without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
2
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 25 publications
6
27
2
7
Order By: Relevance
“…In cases when there are no clinical signs of liver damage, there is always a characteristic histopathological change (6,8,12). Consistent with those studies, our results are similar in that the liver enzymes were increased.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In cases when there are no clinical signs of liver damage, there is always a characteristic histopathological change (6,8,12). Consistent with those studies, our results are similar in that the liver enzymes were increased.…”
Section: Discussionsupporting
confidence: 92%
“…Our data showed that the AST and ALT levels were elevated approximately 5-fold above the normal limits, a finding that is consistent with the existing literature (6,14,15). Elevations greater than 10-fold over the normal levels are less likely (16), but our results have shown that the AST levels in 3.9% of patients and ALT levels in 9.8% of patients were greater than 10-fold the normal levels, which correlates with the results of Yang et al (12). The incidence of serum ALT levels greater than 1000 IU/L was similar to the result of a previous study (17).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…primer EBV enfeksiyonu ile birlikte hepatit gelişen 36 hastayı değerlendirdikleri retrospektif çalışmada, ateş yüksekliğini %83, servikal lenfadenopati %77,8, hepatomegali %30,6 ve splenomegaliyi %27,8 olarak bulmuşlar, ikterik hepatit tablosunda olan iki hasta (%5,6) bildirmişlerdir. 14 Klinik yakınma ve bulgular deerlendirildiğinde ça-lışmamızda benzer sonuçlar elde edilmiş olup, ikterik hepatit % 6,5 oranında görülmüştür.…”
Section: Bulgularunclassified
“…Наибольшее число исследований по проблеме герпесвирусных гепатитов посвящено цитомега-ловирусным (ЦМВ) и гепатитам, обусловленным вирусом Эпштейна -Барр [2,3,[6][7][8]. В послед-ние годы приводятся данные о поражении пече-ни, вызванные вирусами герпеса человека 6-го типа (ВГЧ-6), с возможностью развития хрони-ческого гепатита и формирования цирроза пече-ни [2,3,9,10].…”
Section: Introductionunclassified